Piroplasm Infection in Domestic Cats in the Mountainous Region of Rio de Janeiro, Brazil - Palmer, João Pedro; Gazêta, Gilberto; André, Marcos [UNESP]; Coelho, Aline; Corrêa, Laís; Damasceno, José; Israel, Carolina; Pereira, Rafael; Barbosa, Alynne (My University, 2022)
Piroplasm infections in domestic cats have been reported with increasing frequency in numerous countries. However, in some states of Brazil, little information is available about the occurrence of these parasites. Blood samples were collected from 250 cats treated at a private clinic in the mountainous region of Rio de Janeiro. The samples were each subjected to a blood count, microscopic examination, and molecular research on piroplasms. The animals’ clinical histories and epidemiological information were analyzed to identify the risk factors associated with infection. Ticks were recovered during the clinical care and were identified and subjected to molecular analyses to determine the presence of piroplasm DNA. Piroplasms were detected in 2.7% (7/250) of the cats. Nucleotide sequences of Babesia vogeli were identified in six cats, while the Cytauxzoon sp. was identified in one cat. Cats displaying apathy/weakness/prostration and hemorrhage/bleeding were more likely to be infected. In addition, Amblyomma aureolatum was recovered from a cat PCR-negative for piroplasms. This is the first study in Rio de Janeiro that has detected Babesia vogeli in cats. The results obtained here underscore the need for further studies in Rio de Janeiro to investigate the dynamics of such infections and the vectors involved.
Keywords: Brazil; cats; PCR; piroplasms; Rio de Janeiro